The Doubloon: Trilling's Melville Problem - Monteiro, George (Canadian Review of American Studies, 1986)
Writing about his Partisan Review years, William Barrett retails an anecdote about the reaction of Philip Rahv and Delmore Schwartz to the news that Alfred Kazin was about to turn his critical attention to the works of Herman Melville. "I wonder what Alfred will make of Moby Dick" asked Rahv, "when he turns all that Jewish schmaltz loose on Captain Ahab and the White Whale." The question brought laughter and inspired Schwartz to strike a harpooner's pose in hot pursuit of the great white whale, shouting "Whale ahoy!" Then, heaving his imaginary harpoon, Schwartz yelled out gleefully, "Gefilte fish!"1